EFEKTIFITAS RENDAM KAKI DENGAN REBUSAN JAHE TERHADAP PENURUNAN TEKANAN DARAH PADA IBU HAMIL DENGAN PREEKLAMPSIA DI WILAYAH KERJA PUSKESMAS ROGOTRUNAN - Anisah Khodijah; Fahrianingsih Fahrianingsih; Homsiatur Rohmah (NHM PRESS, 2023)
The number of maternal deaths based on data compiled from the family health program records at the Indonesian Ministry of Health shows 4,627 deaths in Indonesia. This number shows an increase compared to 2019 which was 4,221 deaths. Based on the causes, the majority of maternal deaths in 2020 were caused by bleeding as many as 1,330 cases, hypertension in pregnancy as many as 1,110 cases, and circulatory system disorders as many as 230 cases. Hypertension in pregnancy or Pre-Eclampsia/Eclampsia is a syndrome that occurs in pregnant women with gestational age > 20 weeks which is characterized by an increase in blood pressure to 140/90 mmHg, proteinuria and/or edema. This research is a quasi-experimental research with Non equivalent Control Group Design. The data were taken by measuring the blood pressure of the patients pre and post in the intervention and control groups in the Rogotrunan Health Center working area in August 2022. The number of research samples was 10 respondents who were divided into 5 intervention groups and 5 control groups based on inclusion and exclusion criteria. Analyzed and tested Wilcoxon and paired t test using SPSS ver 2.0. The majority of respondents are of productive age between 34-35 years, the majority of respondents have high school education, the majority of respondents are housewives and the majority of respondents are multiparous mothers. The difference in blood pressure of preeclampsia in the intervention and control groups has a value of p <0.05, namely p = 0.000, so H0 is rejected and Ha is accepted. The results showed that soaking the feet with ginger decoction was effective in lowering blood pressure in pregnant women with preeclampsia.